أنواع محبطات الأعمال الواردة في السنة النبوية: Types of Business Discouragements Mentioned in the Prophetic Sunnah - Muhammad Farhan Salim; Yasir bin Abdillah Al-Salman (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This is a brief research on the types of nullification mentioned in the prophetic texts, and I named it: